Akit Cultural Centre Di Pekanbaru Dengan Pendekatan Arsitektur Kontemporer Sebagai Landasan - Mohamad Rafsanjani; Gun Faisal; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Akit tribe is one of the indigenous tribes of Riau Province that is rich in culture. Hamidy (1991) states that the Akit tribe is included in one of the six isolated tribes in Riau Province. The entry of transmigration from various regions in Indonesia made the Akit tribe's culture and architecture increasingly marginalized and lost. Then an effort was made to resolve this problem by carrying out the design of Akit Cultural Centre located in Pekanbaru City.Akit Cultural Centre is a means to accommodate the Akit ethnic culture which will be presented to the wider community, especially the people of Riau. Akit Cultural Centre is designed to be able to provide information, knowledge, education, training and learning in form, combining the culture of the Akit tribe with Contemporary Architecture.Contemporary architecture is an architecture whose buildings are designed by following a building that is developing in its time or commonly called the present building, so that it presents buildings that can present culture well and interesting forms so that it brings the wider community, especially the younger generation, to revive the existence of the Akit tribe culture.To present a contemporary cultural center, this design goes through processes such as the analysis and application of the theme of Contemporary Architecture which involves many aspects to present the Akit Cultural Center that can solve this problem.Keywords: Cultural Centre, Akit tribe, Contemporary Architecture.